1940
DOI: 10.1084/jem.71.6.765
|View full text |Cite
|
Sign up to set email alerts
|

Ii. Poliomyelitic Virus in Urban Sewage

Abstract: In two out of three large urban epidemics of poliomyelitis the virus of this disease has been detected in samples of sewage. From one of the sites it was found repeatedly. Both positive sites were located in the vicinity of isolation hospitals, and we believe that the findings indicate that this virus can be transported, for short distances at least, through the medium of flowing sewage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0
1

Year Published

1941
1941
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(30 citation statements)
references
References 6 publications
0
29
0
1
Order By: Relevance
“…In the 1940s, several investigators confirmed that the virus responsible for this disease could be found in wastewater (Kling et al, 1942;Melnick, 1947;Paul et al, 1940;Trask and Paul, 1942). For example, it had long been recognized that poliomyelitis was transmitted via the fecal-oral route.…”
Section: Use Of Coliform As An Indicator Of the Presence Of Wastewatermentioning
confidence: 99%
“…In the 1940s, several investigators confirmed that the virus responsible for this disease could be found in wastewater (Kling et al, 1942;Melnick, 1947;Paul et al, 1940;Trask and Paul, 1942). For example, it had long been recognized that poliomyelitis was transmitted via the fecal-oral route.…”
Section: Use Of Coliform As An Indicator Of the Presence Of Wastewatermentioning
confidence: 99%
“…As primeiras tentativas bem sucedidas de isolamento de vírus da poliomielite de esgotos datam dos trabalhos de PAUL; TRASK; CULOTA 18 (1939) e PAUL; TRASK ; GARD 19 (1940). Posteriormente, surgiram numerosas publicações sôbre o assunto não só em relação ao vírus da poliomielite (MELNICK 15 , 1947; RHO-DES et alii 21 , 1950) como a outros enterovirus (CLARK et alii 5 , 1951; KELLY 10 , 1953; POSKANZER & BEADENKOPF 20 , 1961; WILCOX et alii 24 , 1961).…”
Section: Introductionunclassified
“…Since that statement was published, 15 All enteric viruses share a number of years have elapsed, and during the in-common characteristics: terim only one outbreak of poliomyelitis in the United States (3) and one 1. They are excreted in feces in outbreak in Canada (4) have been at-large numbers.…”
mentioning
confidence: 99%
“…Kling (7) proposed his theorie hydrique, or theory of the waterborne transmission of poliomyelitis, in 1929. The concept did not gain much support until the late 1930's and early 1940's, when poliovirus was discovered in the feces of ill persons, in apparently normal healthy individuals (8)(9)(10)(11)(12)(13), and in urban sewage (14)(15)(16)(17)(18). Kling's subsequent isolation of poliovirus from well water in 1939-40 (19) attracted little attention, probably because of the unusual circumstances under which the virus was found-that is, on the day following the recognition of a clinical case of poliomyelitis in a member of the family using the well.…”
mentioning
confidence: 99%